Schistosomiasis Among Female Migrants in Non-endemic Countries: Neglected Among the Neglected? A Pilot Study - Roure, Sílvia; Pérez-Quílez, Olga; Vallès, Xavier; Valerio, Lluís; López-Muñoz, Israel; Soldevila, Laura; Torrella, Ariadna; Fernández-Rivas, Gema; Chamorro, Anna; Clotet, Bonaventura (Frontiers in Public Health, 2022)
Background: Schistosomiasis among migrant populations in Europe is an underdiagnosed infection, yet delayed treatment may have serious long-term consequences. In this study we aimed to characterize the clinical manifestations of Schistosoma infection among migrant women, and the degree of underdiagnosis . Methods: We carried out a prospective cross-sectional study among a migrant population living in the North Metropolitan Barcelona area and coming from schistosomiasis-endemic countries. We obtained clinical, laboratory and socio-demographic data from electronic clinical records, as well as information about years of residence and previous attendance by the health services. Blood sample was obtained and schistosomiasis exposure was assessed using a specific ELISA serological test. Results: Four hundred and five patients from schistosomiasis-endemic regions were screened, of whom 51 (12.6%) were female. Seropositivity prevalence was 54.8%, but considering women alone we found a prevalence of 58.8% (30 out of 51). The median age of the 51 women was 41.0 years (IQR [35-48]) and the median period of residence in the European Union was 13 years (IQR [10-16]). Schistosoma-positive women (N=30) showed a higher prevalence of gynaecological signs and symptoms compared to the seronegative women (96.4% vs. 66.6%, p = 0.005). Among seropositive women, the median number of visits to Sexual and Reproductive Health unit prior to diagnosis of schistosomiasis was 41 (IQR [18-65]). Conclusion: The high prevalence of signs and symptoms among seropositive women and number of previous visits suggest a high rate of underdiagnosis and/or delayed diagnosis of Schistosoma infection, particularly female genital schistosomiasis, among migrant females.